Motion and kinematics parameters of frozen-thawed bovine spermatozoa assessed by Biovis CASA - Pathak, P K; Dhami, A J; Chaudhari, Dinesh V; Patel, Jagdish A (Indian Journal of Dairy Science, 2019)
This study was carried out on semen of nine healthy mature breeding bulls (3 each of Gir, Surti and Murrah breed) to evaluate the motion characteristics and kinematics of their frozen-thawed sperms by using computer assisted semen analyzer (CASA). The ejaculates (n=72, 24 of each breed) having >75% initial motility were diluted @ 80 million sperm/ml using TFYG extender, packaged in French mini straws using IS4 machine, equilibrated for 4 hrs and were frozen in liquid nitrogen vapour using biofreezer. The straws were thawed in water-bath at 37°C for 30 seconds. The motion characteristics of frozen-thawed semen assessed by CASA revealed same pattern as of fresh semen. The mean values of total motile sperms, rapid, slow & non-progressive motile sperm and immotile sperms in Gir, Surti and Murrah bulls’ semen were 58.22 ±1.71, 64.44±1.58 and 67.84±1.54 %; 17.93±1.56, 17.13±2.49 and 21.47±2.70 %; 23.90±1.70, 30.64±2.06 and 30.47±2.25 %; 16.23±1.24, 16.70±1.58 and 15.90±1.52 %, and 41.95±1.71, 35.56±1.58 and 31.73±1.62%, respectively. The overall mean velocity parameters based on total motile sperms of frozen-thawed semen of Gir, Surti and Murrah bulls were: average path velocity (VAP) 42.14±1.21, 40.15±1.58 and 42.41±1.62 µm/s; curvilinear velocity (VCL) 78.22±2.01, 76.52±2.31 and 80.25±2.25 µm/s, straight line velocity (VSL) 35.60 ±1.18, 33.69±1.59 & 36.19 ±1.58 µm/s; linearity 45.21±1.62, 44.38±2.05 and 44.96± 1.35 %; straightness 78.53±1.17, 78.75±1.40 and 80.24±1.13 %; wobbling index 57.86±1.69, 56.78±1.88 and 56.55±1.29 %; beat-cross frequency (BCF) 11.77±0.67, 12.08±0.72 and 12.64±0.86 hz; amplitude of lateral head displacement (ALH) 2.18±0.17, 2.30±0.15 and 2.35±0.15 µm; dancing frequency (DNC)  185.08±15.96, 183.90±14.22 and 198.44±15.64 µm2/s, and dancing mean (DNM) 4.96±0.51, 5.35±0.54 and 5.32±0.51 µm2/s, respectively. None of these traits differed significantly between breeds/ species or between bulls in any of the breed. The sperm velocity parameters recorded based on progressively motile sperms revealed almost similar pattern and variation to those found based on total motile sperms, but the values of all velocity parameters for progressive motile sperms were higher than those of total motile sperms in all three breeds when assessed through CASA.